2004
DOI: 10.1091/mbc.e04-03-0264
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorylation of Vinculin on Tyrosine Residues 100 and 1065, Mediated by Src Kinases, Affects Cell Spreading

Abstract: Vinculin is a conserved actin binding protein localized in focal adhesions and cell-cell junctions. Here, we report that vinculin is tyrosine phosphorylated in platelets spread on fibrinogen and that the phosphorylation is Src kinases dependent. The phosphorylation of vinculin on tyrosine was reconstituted in vanadate treated COS-7 cells coexpressing c-Src. The tyrosine phosphorylation sites in vinculin were mapped to residues 100 and 1065. A phosphorylation-specific antibody directed against tyrosine residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
111
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(122 citation statements)
references
References 64 publications
9
111
2
Order By: Relevance
“…Vinculin activity is controlled by a high affinity interaction between the head and tail domains (34). Its activation and recruitment to force-activated talin (and likely to ␣-catenin) involve phosphorylation and allosteric interactions with cytosolic binding partners (34,61,63,64). Conversely, recent experimental data demonstrated that force directly activates ␣-catenin (30,42), and the present simulations suggest that this occurs by a process involving salt-bridge disruption within the M region.…”
Section: Salt-bridgesmentioning
confidence: 50%
“…Vinculin activity is controlled by a high affinity interaction between the head and tail domains (34). Its activation and recruitment to force-activated talin (and likely to ␣-catenin) involve phosphorylation and allosteric interactions with cytosolic binding partners (34,61,63,64). Conversely, recent experimental data demonstrated that force directly activates ␣-catenin (30,42), and the present simulations suggest that this occurs by a process involving salt-bridge disruption within the M region.…”
Section: Salt-bridgesmentioning
confidence: 50%
“…Previousinvestigatorshavesuggestedthatvinculinphosphorylation at Tyr 1065 may contribute to the regulation of its conformation (37,48). Although vinculin has long been recognized as a tyrosine phosphorylation substrate (49), Zhang et al (37) were the first to map one of the phosphorylation sites to Tyr 1065 near the C terminus of the molecule within the tail domain and to demonstrate that phosphorylation at this site, as well as at Tyr 100 , affects cell spreading in activated platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Although vinculin has long been recognized as a tyrosine phosphorylation substrate (49), Zhang et al (37) were the first to map one of the phosphorylation sites to Tyr 1065 near the C terminus of the molecule within the tail domain and to demonstrate that phosphorylation at this site, as well as at Tyr 100 , affects cell spreading in activated platelets. They also used pull-down assays to analyze the effect of Tyr 1065 phosphorylation on the affinity of vinculin tail domain fragments for the head domain and found that the phosphorylation markedly reduced the affinity of the tail domain for the head domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations